Do the Disclosure of Environmental Management Accounting and Independent Assurance Affect Profitability? - Hempry Putuhena; Leonard D. M. Sangur; M. Rifkhi Fauzan S; Paskanova C Gainau (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of water usage, energy consumption, carbon emissions produced, waste generated, independent Assurance, and environmental expenditures on Return On Equity. (ROE). This study provides information about entities that are socially responsible and whether their financial performance will improve or not after the implementation of corporate social and environmental activities. The independent variables in this study are water usage, energy consumption, carbon emissions produced, waste generated, independent Assurance, and environmental expenditures. ROE in this study is the dependent variable. The secondary data required for the study comes from the sustainability reports of 35 companies in 2023, and then the relationship between the independent and dependent variables is tested using EViews. The results of data management in the study indicate that there is an effect between water usage, waste generated, and environmental expenditures on ROE, thus supporting H1, H4, and H6. This condition is reversed with energy consumption, carbon emissions produced, and independent Assurance, where these three variables do not have an effect on ROE, proving that H2, H3, and H5 are not supported. The implication of this study is that management can achieve sustainable profits by disclosing activities that support environmental sustainability and using independent parties to guarantee the sustainability reports that have been created, thereby gaining more trust from stakeholders, which affects ROE.